Elastic Aerogels of Cellulose Nanofibers@Metal–Organic Frameworks for Thermal Insulation and Fire Retardancy - Zhou, Shengyang (Nanomicro Lett, 2019)
Metal–organic frameworks (MOFs) with high microporosity and relatively high thermal stability are potential thermal insulation and flame-retardant materials. However, the difficulties in processing and shaping MOFs have largely hampered their applications in these areas. This study outlines the fabrication of hybrid CNF@MOF aerogels by a stepwise assembly approach involving the coating and cross-linking of cellulose nanofibers (CNFs) with continuous nanolayers of MOFs. The cross-linking gives the aerogels high mechanical strength but superelasticity (80% maximum recoverable strain, high specific compression modulus of ~ 200 MPa cm(3) g(−1), and specific stress of ~ 100 MPa cm(3) g(−1)). The resultant lightweight aerogels have a cellular network structure and hierarchical porosity, which render the aerogels with relatively low thermal conductivity of ~ 40 mW m(−1) K(−1). The hydrophobic, thermally stable MOF nanolayers wrapped around the CNFs result in good moisture resistance and fire retardancy. This study demonstrates that MOFs can be used as efficient thermal insulation and flame-retardant materials. It presents a pathway for the design of thermally insulating, superelastic fire-retardant nanocomposites based on MOFs and nanocellulose. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40820-019-0343-4) contains supplementary material, which is available to authorized users.